LESSON STUDY: PENINGKATAN SOFT SKILLS CALON GURU MATEMATIKA - Fina Hanifa Hidayati (Program Studi Pendidikan Matematika, FKIP Universitas Muhammadiyah Cirebon, 2020)
Abstract Preparation is needed for every teacher even pre-service teachers to teach mathematics. Soft skills which is related to the ability to cooperate, communicate, initiative, ability to lead, assist, independent effectiveness, plan and organize, and the ability to present is needed in an effort to improve the quality of pre-service teachers. Lesson Study was carried out in an effort to improve the soft skills of 30 pre-service mathematics teacher. This is a qualitative descriptive study using observation sheet and soft skills assessment during Lesson Study process. Group interview forum also used to explore research data. The implementation of Lesson Study had enhanced soft skills and foster readiness and built innovation in the preparation of the mathematics learning implementation for pre-service mathematics teachers. Keywords: lesson study, soft skills, pre-service mathematics teachers. Abstrak Sebagai calon guru matematika diperlukan persiapan yang matang secara menyeluruh untuk mengajarkan matematika. Soft skills yang kaitannya dengan kemampuan bekerjasama, berkomunikasi, inisiatif, kemampuan untuk memimpin, mendampingi, efektivitas mandiri, merencanakan dan mengorganisasi, serta kemampuan dalam presentasi diperlukan dalam upaya peningkatan kualitas calon guru. Lesson Study dilaksanakan dalam upaya peningkatan soft skills 30 mahasiswa calon guru matematika. Penelitian ini merupakan penelitian deskriptif kualitatif dengan menggunakan instrumen lembar observasi dan penilaian soft skills selama proses Lesson Study. Forum grup interview juga dilaksanakan untuk menggali data penelitian. Pelaksanaan Lesson Study telah meningkatkan soft skills dan menumbuhkan kesiapan dan menciptakan inovasi dalam persiapan pelaksanaan pembelajaran matematika bagi calon guru matematika. Kata kunci: lesson study, soft skills, calon guru matematika